Intensity of badminton (shadow) drill and badminton match - Ng, Kai Cong (Nanyang Technological University, 2021)
Background: Shadow Badminton is a commonly used drill that coaches implement in their training regime to improve players’ footwork and agility (Nirendan & Murugavel, 2019). However, there is a lack of study in comparing the fitness parameters of shadow badminton drills to actual badminton matches. Purpose: This study aims to investigate the difference between the intensity of patterned shadow badminton drill and badminton match by measuring the heart rate of the participants. Hypothesis: There is a correlation between the intensity of shadow badminton drill and badminton match. Methodology: Eight school/ hall team badminton players (4 men and 4 women) from Nanyang Technological University (NTU) / National Institute of Education (NIE) were recruited. In this study, participants had completed two sessions: i) patterned shadow badminton drill and ii) 3 sets match play. Paired t-test was used to determine the difference in heart rate between shadow badminton drill and match play. Results: The average heart rate for the shadow badminton drill and match play were 141.9 and 171.2 for men, and 155.9 and 173.6 for women respectively. There was a significant difference (p < .001) between the intensity of the shadow badminton drill and match play for both the men and women. Discussion: The findings from this study indicated a higher average heart rate for the match play as compared to the recommended shadow badminton drill. Conclusion: The intensity of the match play was higher than the intensity of the shadow badminton drills despite a shorter duration of the match play as compared to the shadow badminton drills.